Kradzież szczególnie zuchwała (art. 278a § 1 k.k.) - Kluza, Jan (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article is a critical analysis of the newly introduced oﬀ ence of particularly au-dacious theft (Article 278a § 1 of the Criminal Code), which constitutes a return to the regulation contained in the penal code of 1969 in force in the Polish People’s Republic. Executive features are deﬁ ned in the glossary of statutory expressions in Article 115 § 9a of the Penal Code, which, however, does not change the fact that these signs were formulated in a judgemental and blurred way. Notwithstanding this, such a signiﬁ cant diﬀ erentiation of criminal liability by returning to the solutions of the 1969 Code is un-justiﬁ ed.
Keywords: kradzież; kradzież szczególnie zuchwała; typ kwalifikowany; przestępstwa przeciwko mieniu